Stakeholders’ Perspectives on The Development of Rindu Hati Tourism Destination Village in Bengkulu Province, Indonesia - Andi Makhrian; Fachri Eka Saputra (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2021)
Rindu Hati village is one of the most potential tourism destination villages in Bengkulu Province, Indonesia. The most outstanding features of Rindu Hati village are river rafting and glamping, offering natural environmental scenery, an exceptionally adventurous, and wilderness experience. This research aims to identify stakeholders’ perspectives on the development of Rindu Hati tourism destination village in socio-cultural empowerment, environmental quality, economic growth, and tourists’ satisfaction post-visit. The development of the tourism destination village is viewed from multiple stakeholders' perspectives, including visitors, destination management, the surrounding community, and local government. A qualitative research design was used to answer the research questions. Several informants engaged with Rindu Hati tourism destination village were interviewed to collect data. The results show various stakeholders’ perspectives on the sustainable development of Rindu Hati tourism destination village. Destination management and the surrounding community carry out their respective roles in village development, while the local government has not yet assisted in village development. Issues regarding waste, local wisdom, and preserving the natural environment discussed in this research become the community and destination managers' concerns.